1995
DOI: 10.1093/intimm/7.11.1861
|View full text |Cite
|
Sign up to set email alerts
|

Migration pathways of CD4 T cell subsets in vivo: the CD45RC- subset enters the thymus via α4 integrin-VCAM-1 interaction

Abstract: The present investigation examines the localization and migration of purified T cell subsets in comparison with B cells, CD8 T cells and CD4+ CD8- single-positive thymocytes. CD4 T cell subsets in the rat are defined by mAb MRC OX22 (anti-CD45RC), which distinguishes resting CD4 T cells (CD45RC+) from those (CD45RC-) which have encountered antigen in the recent past--subpopulations often referred to as 'naive' and 'memory'. Purified, 51Cr-labelled CD45RC+ CD4 T cells broadly reflected the migration pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…There Was clearly an increase in the number of cells which migrated into the thymus following antigen-specific T cell activation in the periphery, confirming the findings of earlier studies (Naparstek et al, 1982;Fink et al, 1984;Agus et al, 1991;Bell et al, 1995;Westermann et al, 1996). This increase amounted to about 16 to 20-fold 3 days after injection with peptide.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…There Was clearly an increase in the number of cells which migrated into the thymus following antigen-specific T cell activation in the periphery, confirming the findings of earlier studies (Naparstek et al, 1982;Fink et al, 1984;Agus et al, 1991;Bell et al, 1995;Westermann et al, 1996). This increase amounted to about 16 to 20-fold 3 days after injection with peptide.…”
Section: Resultssupporting
confidence: 88%
“…More recently, it was shown that blasts (generated in parent F combinations) homed to the thymus, and represented approximately 0.4% of mature T thymocytes, although the rate of homing was greatly increased by irradiation of hosts (Agus et al, 1991). Others have shown that, compared to 'naive' CD4 + T cells, there is a preferential accumulation of antigen-experienced T cells in the rat thymus (Bell et al, 1995;Westerman et al, 1996). As is the case for 'normal' peripheral T cells (Hirokawa et al, 1989), accumulation of activated cells within the thymus is largely restricted to the medulla (Pabst and Binns, 1989;Agus et al, 1991;Westermann et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of the method of thymus FITC injection is that recirculating mature lymphocytes, and particularly those that have been previously activated, continuously enter the thymus as shown in many studies [6][7][8][9][10][11][12][13][14][15] and would also be labeled. Many of the FITC-labeled cells that leave the thymus and are detected peripherally could therefore be mature recirculating T cells, rather than cells that recently matured in the thymus.…”
Section: Introductionmentioning
confidence: 99%
“…To discriminate between END-containing memory versus naive T cells, cells from LN and the circulation were collected as described previously. T-helper cells (CD4) are comprised of two subsets: naive and memory cells (18). Since antibodies against rat memory T cells were not available, we first stained these cells with an antibody against END and then with an antibody against all T-helper cells (CD4 ϩ ).…”
Section: Introductionmentioning
confidence: 99%
“…In another experiment, we stained for END and for naive T cells (CD45RC ϩ ). We hypothesized that if END-containing cells stain for CD4 but infrequently stain for CD45RC, then END ϩ /CD4 ϩ cells would be predominantly END-containing memory-type T cells (18). Immune cells (5 ϫ 10 6 cells/tube) were examined for coexistence of CD4 and END by double staining with FITC-preconjugated anti-CD4 (W3/25) and a rabbit antibody to END, followed by an IgG secondary goat anti-rabbit antibody preconjugated with Texas red.…”
Section: Introductionmentioning
confidence: 99%